The Effectiveness of Police Patrols in Efforts to Reduce Criminality at Labuhanbatu Resort Police - Hendra Sony Rambe; Sriono Sriono; Kusno Kusno (Budapest International Research and Critics University, 2021)
One of the state threats due to the Covid-19 case is the disturbance of the stability of the security of public order due to the occurrence of crime. Cumulatively, there is an increase in criminal cases in Indonesia in 2020 compared to 2019. The dominating cases are cases of narcotics abuse, then cases of weighted theft, theft of two-wheeled motor vehicles and cases of theft with violence. The main role and duties of the National Police are at realizing domestic security which includes maintaining security and public order, law and order, providing protection, protection and services to the community and upholding human rights. Police patrol is one of the roles of the police in an effort to reduce the crime rate. The implementation of police patrols at the Labuhanbatu Police in an effort to suppress crime in the jurisdiction of the Labuhanbatu Police, namely: Exploring the areas, routes and targets that have been determined and seeing any vulnerabilities. Taking the First Action at the Place of the Case, Committing Minor Crime, Labuhanbatu Police carried out Tipiring in case of being caught red-handed. Limited repressive actions were taken when there was disruption of social security and security. Police patrols are effective in reducing the crime rate at the Labuhanbatu Police. The obstacles that exist are Labuhanbatu Police personnel not proportional to the population, insufficient patrol operational funds, inadequate patrol equipment, and the community is not proactive in helping the police work in reducing the crime rate.